Knowledge organisation and digital preservation of ‎cross-cultural musical heritage: A Chinese piano music ‎collection - Zhang, Dan; Xin, Ye (Malaysian Journal of Library and Information Science, 2025)
Chinese piano music represents a significant case study in cross-cultural knowledge integration, yet its organisation within library systems remains insufficiently addressed. This research examines the challenges of information management in documenting Chinese piano compositions that incorporate Western compositional techniques from the early twentieth century to the present. Employing mixed methods, combining bibliometric analysis of 856 publications, systematic review of digital music archives, and comparative metadata analysis across 45 international music libraries. This study develops a comprehensive framework for cross-cultural musical resource organisation. Results reveal substantial gaps in current cataloguing systems, with only a small proportion of major digital music libraries implementing adequate metadata schemas for hybrid compositional styles. The study proposes an enhanced metadata framework incorporating taxonomies of compositional techniques, cultural context descriptors, and temporal evolution markers, validated through expert panel assessment. Findings indicate improved discoverability and user satisfaction when specialised metadata is implemented. This research provides evidence-based guidelines for managing multicultural music collections, developing culturally sensitive classification systems, and enhancing digital preservation strategies for hybrid musical forms, offering practical implications for music librarians, digital archivists, and information professionals managing cross-cultural heritage resources.